The Immunological Regulation Roles of Porcine β-1, 4 Galactosyltransferase V (B4GALT5) in PRRSV Infection - Zhang, Lei; Ren, Jie; Shi, Peidian; Lu, Dong; Zhao, Chengxue; Su, Yanxin; Zhang, Lilin; Huang, Jinhai (Frontiers in Cellular and Infection Microbiology, 2018)
B4GALT5, also known as β-1, 4 galactosyltransferase V, is one of the members of β-1, 4 galactosyltransferase gene (B4GALT) family, which plays an important role in embryonic development, tumor generation and other diseases. In this study, we firstly cloned porcine B4GALT (pB4GALT5) from porcine peripheral blood mononuclear cells, and predicted the structural domain and function of seven porcine β-1, 4 galactosyltransferase (I-VII) based on transcriptome analysis of PRRSV infected cells. Additionally, the upregulated porcine B4GALT5 expression was detected from PRRSV infected porcine alveolar macrophage (PAM) cells. The PRRSV proliferation were slightly inhibited in overexpression of pB4GALT5 transfected cells, the interaction of B4GALT5 and GP5 of PRRSV was firstly be detected by Co-IP, and the co-location between B4GALT5 and GP5 were also observed in golgi membranes by confocal microscopy. A significant increasing mRNA transcription, including inflammatory cytokines (IL-1β,TNF-α, MCP-1, IL-6, IL-18, and IFN-α) and some cell surface glycosylated protein involved in antigen present (MHC-I/II, LFA-1), cell adhesion and migration (chemokine receptor CCR2) were upregulated in B4GALT5 overexpressed PRRSV infected cells. Our results demonstrated that the regulation of pB4GALT5 plays an important roles in PRRSV proliferation and modification function in viral infection cells. And these results will contribute to future studies on the detailed functions and potential underlying mechanisms of β-1, 4 galactosyltransferase V in antiviral immunity.